Kajian Intertektualisasi Syair Puisi ‘I’tiraf Karya Abu Nawas Dengan Lagu Andai Ku Tahu Karya Ungu Band (Analisis Sastra Bandingan) - Lalu Muhamad Rusdi Fahrizal; Tatik Tasnimah (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2022)
Abstract: This study aims to describe the study of the intertextuality of the poem 'I'tiraf by Abu Nawas with the song Andai ku Tahu by Ungu band using comparative literature theory. The research method that the researcher uses in writing this article is a qualitative descriptive approach. Data collection techniques in this study researchers rely on reading and note-taking methods. Reading technique is used to find information related to research. Reading technique is also used as a step in heuristic and hermeneutic reading. The note-taking technique is used as data collection so that it is well organized. The results of this study are the poetry of 'I'tiraf by Abu Nawas and the lyric of the song if I know the work of Ungu band has a comparison of similarities and differences. Comparison of similarities in the poetry of 'I'tiraf' by Abu Nawas and the lyrics of the song if I knew the work of Ungu band including themes, tones, majaz, mandate and concrete words. The difference lies in the physical structure of diction and typography.